Perbedaan Rasio Neutrofil Limfosit Kanker Serviks Tipe Karsinoma Sel Skuamosa Berdasarkan Diferensiasi - Ghaitsa Zahira Shofa; Hariadi Yuseran; F.X. Hendriyono (Homeostasis, 2022)
Abstract: Cervical cancer has several cell types, squamous cell carcinoma, adenocarcinoma and others. The level of progression of cervical cancer is determined by the degree of cell differentiation, which is classified into well, moderate and poor differentiation. The neutrophil lymphocyte ratio (NLR) can assess the progression of cervical cancer. The higher the NLR, the higher the level of progression and the worse the degree of cell differentiation. This research is an analytical study using secondary data. The results obtained were 88 cervical cancer subjects with squamous cell carcinoma type and only 41 subjects (46,6%) included in inclusion criteria of this study. In this study, there were 9 subjects of cervical cancer squamous cell carcinoma type with well-differentiated (22,0%), 26 subjects with moderately differentiated (63,5%) and 6 subjects with poorly differentiated (14,5%). The results of NLR for cervical cancer squamous cell carcinoma type well-differentiated has a mean of 1,5 with standard deviation of 1,2. The results of NLR for cervical cancer squamous cell carcinoma type moderately-differentiated has a mean of 3,4 with standard deviation of 2,3. The results of NLR for cervical cancer squamous cell carcinoma type poorly-differentiated has a mean of 5,5 with standard deviation of 3,7. Conclusion from this study is there was a significant difference of NLR in cervical cancer squamous cell carcinoma type in each differentiation. Keywords: cervical cancer squamous cell carcinoma type; well, moderately and poorly differentiated; NLR Abstrak: Kanker serviks mempunyai beberapa tipe sel, yaitu tipe karsinoma sel skuamosa, adenokarsinoma dan lain-lain. Tingkat progresivitas kanker serviks ditentukan dengan derajat diferensiasi sel, yang dibedakan menjadi diferensiasi baik, sedang dan buruk. Rasio neutrofil limfosit (RNL) dapat menilai progresivitas kanker serviks. Semakin tinggi RNL, maka semakin tinggi juga tingkat progresivitasnya dan derajat diferensiasi selnya semakin buruk. Penelitian ini bersifat studi analitik dengan menggunakan data sekunder. Hasil penelitian diperoleh 88 subjek kanker serviks tipe karsinoma sel skuamosa dan hanya 41 subjek (46,6%) yang memenuhi kriteria inklusi penelitian. Pada penelitian ini, terdapat 9 subjek kanker serviks tipe karsinoma sel skuamosa diferensiasi baik (22,0%), 26 subjek diferensiasi sedang (63,5%) dan 6 subjek diferensiasi buruk (14,5%). Hasil data RNL pada kanker serviks tipe karsinoma sel skuamosa diferensiasi baik memiliki rerata 1,5 dengan simpang baku 1,2. Hasil data RNL pada kanker serviks tipe karsinoma sel skuamosa diferensiasi sedang memiliki rerata 3,4 dengan simpang baku 2,3. Hasil data RNL kanker serviks tipe karsinoma sel skuamosa diferensiasi buruk memiliki rerata 5,5 dengan simpang baku 3,7. Kesimpulannya terdapat perbedaan bermakna RNL pada kanker serviks tipe karsinoma sel skuamosa antar diferensiasi. Kata-kata kunci: kanker serviks tipe karsinoma sel skuamosa; derajat diferensiasi baik, sedang dan buruk; RNL